Glycine-rich cell wall proteins in bean: gene structure and association of the protein with the vascular system. - Keller, B (1988)
A single genomic clone (14 kb) isolated from bean (Phaseolus vulgaris L.) contains two genes that encode glycine-rich proteins. These genes are present as single copies in the genome, are separated by 2.85 kb and encode transcripts of 1.8 kb and 1.0 kb respectively. The encoded proteins contain 60% glycine and have amino-terminal signal peptides. The 1.8 kb transcript is present in young hypocotyls and in ovary tissue. Excision-wounding transiently induced this transcript in old, but not in young hypocotyl tissue. Antibodies raised against regions of the glycine-rich protein 1.8, expressed as a lacZ fusion protein in bacteria, react with a protein of 53 kd in a protein fraction extracted from cell walls of bean ovaries. Tissue imprints of bean ovaries treated with anti-glycine-rich protein antibodies showed that the glycine-rich protein was distributed in a regular pattern of small, highly localized discrete sites. The immunoreactive regions correspond to the pattern of vascular tissue in the pod. In young hypocotyls, glycine-rich protein is present at four pairs of discrete sites symmetrically arranged on the inner side of the vascular ring. These results suggest a close relationship between glycine-rich proteins and development of the vascular system.